Paradoxical relationship in sensorimotor system: Knee joint position sense absolute error and joint stiffness measures - Nagai, Takashi; Bates, Nathaniel A.; Hewett, Timothy E.; Schilaty, Nathan D. (Clinical biomechanics (Bristol), 2019)
Relationships between joint position sense and the sensorimotor characteristics such as joint stiffness, time to detect motion, and time to peak torque during a perturbation test have rarely been investigated due to methodological challenges. The purpose of this study was to compare joint position sense and the sensorimotor characteristics in healthy individuals. A total of 26 subjects were recruited and completed joint position sense and a perturbation test on isokinetic dynamometer. Joint position sense was assessed by comparison of the absolute angle difference between a reference and replicated position. During the perturbation test, the dynamometer moved the knee flexion angle from 70° to 30° (0° represents a full knee extension) at the velocity of 500° per second at random. Subjects were asked to react and pull back the leg as soon as they perceived the movement. Pearson or Spearman's correlation coefficients were used to assess these relationships (P < 0.05). Larger joint position sense absolute error values were significantly correlated with higher short-range at 50 milliseconds (r = 0.572, P = 0.002), at 100 milliseconds (ρ = 0.416, P = 0.035), and reactive joint stiffness (r = 0.395, P = 0.046). There was a paradoxical relationship between higher joint stiffness and worsened joint position sense. Potential reasons include sensory weighting within the sensorimotor system and thixotropic properties (after-effects of muscle eccentric contractions to increase stiffness and alter joint position sense). •Joint position sense is a common proprioception test.•Regulation of joint stiffness is critically important for joint stability.•The relationships between sensory/motor functions have rarely examined together.•Higher position sense error values exhibit higher joint stiffness measurements.•A paradoxical relationship of joint position sense and stiffness is explained.